Pedestrian and its safety in historical area of Banda Aceh : an observation / Irin Caisarina, Sri Anggina Harahap and Hafnidar Bahri - Caisarina, Irin; Harahap, Sri Anggina; Bahri, Hafnidar (2018)
As one of the heritage cities in Indonesia, Banda Aceh must pay attention to the historical area in order to maintain the region's historical values as mandated in the "Program Penataan dan Pelestarian Kota Pusaka (P3KP)". Maintaining the preservation of the area is not only done by preserving its cultural heritage, but also by maintaining the stability of its area, such as maintaining the existence of the region by creating an area for pedestrians to enjoy the historical area. The pedestrian infrastructure facilities need to be properly provided in accordance with the applicable rules, so that a vibrant envinroment of walking surrounding historical area can be created. This paper analysed the existing condition in Banda Aceh historical area. An observation was conducted in pedestrians sidewalk around the historical area by observing the design and safety aspects. Based on the field observations, not all pedestrian way designs have complied with the design aspects and criteria for pedestrian. Likewise with safety, some primary roads are not equipped with crossing zones, and existed crossing zones do not seem to use traffic signal. Several suggestions to impose traffic policy in this area such as using traffic calming by limiting the speed of vehicles in primary road in this area and limiting vehicle parking in public space area by allocating street parking in the nearby area.